Death education for children and young people in public schools. (2nd October 2020) - Friesen, Hannah; Harrison, Jennifer; Peters, Melissa; Epp, Donna; McPherson, Nancy
Abstract: Background: Conversations about death are often associated with fear, anxiety, avoidance and misunderstandings. Many adults feel that these discussions are inappropriate and confusing for young people. In this project, two fourth-year nursing students partnered with a local palliative care team to examine death education for children. The nursing students focused on children's understandings of death and their coping abilities, the lack of appropriate discussions about death with children, and the implementation of death education in public schools. Three online death education resources were identified and evaluated for use in public schools. This project fueled preliminary local discussions and advocacy efforts in the provision of death education for children. In the future, death education will need to be incorporated into education plans at local schools, and could be done in collaboration with the local palliative care team.